Analisis Kesulitan Siswa Pada Penyelesaian Masalah Pemfaktoran Aljabar di Kelas VIII - Dwi Noviani Sulisawati; Indah Rahayu Panglipur (Universitas Islam Jember, 2022)
The research aim to describe the types of learning difficulties by students while solving the problems of algebraic factoring in class VIII. This research is a type of qualitative research with an exploratory approach. This study is intended to reveal, analyze and provide an overview of the difficulties experienced by class VIII students while solving algebraic factoring problems with the research subjects being 3 junior high school students who had the lowest scores when working on problems. To ensure the validity of the data obtained, this study uses source triangulation to compare and double-check the degree of trustworthiness of the information obtained. After analyzing the data regarding the difficulties experienced during solving the problemsof algebraic factoring, it was concluded that the difficulties experienced by students were (1) Unable to distinguish coefficients, constants, and terms; (2) The subject has difficulty in performing operations with positive and negative integers; (3) The subject does not know the value of a variable; (4) The subject does not know the next steps when solving the problem; (5)The subject does not know the steps to do after completing the distributive step and (6) The subject cannot find two numbers instead of bx with . Keywords: learning difficulties, problem solving, algebraic factoring